Program “I’dad Lughowi” dalam Upaya Membekali Kemampuan Bahasa Arab Mahasiswa STIBA Ar-Raayah, Sukabumi (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2026)
Nowdays, Arabic already has its own charm. Apart from the Al-Quran and Hadith as sources of Islamic Shari'a which are imported from the original source in Arabic, the emergence of scientific disciplines linked to Shari'a adds to the public's attraction and interest in studying Shari'a directly from its Arabic sources. Arabic language learning is starting to emerge with various strategies and methods applied. Some are successful and others need review. In this article, the author wants to examine Arabic language learning in the STIBA Ar-Raayah i'dad lughowi program which is considered successful because it has produced many regional, national and even international achievements. This article aims to examine the background of students in the STIBA Ar-Raayah i'dad lughowi program, the teaching and learning activities of the i'dad lughowi program at STIBA Ar-Raayah and the examination system implemented in the i'dad lughowi program. This article is a case study at STIBA Ar-Raayah using a descriptive qualitative approach. The results found in this research are (1) the background of students in the STIBA Ar-Raayah i'dad lughowi program who come from various regions and schools, (2) learning using the Arabiyyah book Baina Yadaik by maximizing the direct method and activities outside the classroom, (4) a unique exam system with Al-Qur'an exams, subject exams, syahri exams, nihai exams, as well as a rosib system for students who do not reach the minimum completion criteria. The results and conclusions of this research can be used as a reference for Arabic language educational institutions to make them more effective in the future.
Keywords: Arabic Language, Language Preparation, STIBA Ar-Raayah.